POLITICAL MARKETING IN THE ELECTION FOR GOVERNOR IN THIS DIGITAL AGE - William, Reynold; Nur Endah Retno Wuryandari (Dinasti International Journal of Management Science, 2020)
After reformation era, there is a very significant shift towards the political life in Indonesia. So politicians and political parties need to redesign competing strategies to win political competition. The purpose of this study is to find out whether the Personal Branding, Political Marketing, Politic of Identity and Social Media have an influence on the decision of the community's option. The unit of analysis which been studied was the individuals, they are the individuals who had taken part in the general election of the West Java election. There are 216 respondents with dissemination in 5 cities (Bekasi, Bandung, Tasikmalaya, Bogor, Depok) and 1 district (Garut). The result, Political Marketing and Politic of Identity have a positive and significant effect on the decision of the communities. Personal Branding and Social Media have a positive but not significant effect on the decision to vote.